PARAFILIA: NATURE ATAU NURTURE? TINJAUAN TEOLOGIS DAN PSIKOLOGIS - Fathonah K. Daud (UIN Raden Mas Said Surakarta, 2016)
The discourse of paraphilia has become public attention. Enforcing religious values and sex education since on the early stage is an inevitable need by the society. Theologically and psychologically, there are paraphilia which characteristically given (nature) and also nurture or affected by its environment. This article tries to explore the existence of paraphilia, theologically based on Islamic law and physiologically, which is for longtime based on the societal norm judged as deviant, but today the norm was questioned, even criticized through the reason of human right. Even theologically, Islamic teaching has clearly prohibited sexual relation which is not properly following the sharia law.